2002
DOI: 10.1139/l02-010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sealers in counteracting alkali-silica reaction in highway median barriers exposed to wetting and drying, freezing and thawing, and deicing salt

Abstract: This study follows another experimental study where different types of sealers were applied on plain and air-entrained large concrete cylinders made with high-alkali contents and highly alkali–silica reactive limestone aggregates. The main objective was to determine the effectiveness of these sealers in counteracting concrete expansion and surface deterioration due to alkali–silica reaction under various exposure conditions. This study indicated that all three sealers tested, the silane-, oligosiloxane-, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Concrete expansion due to ASR will only occur when the internal relative humidity of the concrete is greater than 80 percent [3,4].…”
Section: Mitigation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concrete expansion due to ASR will only occur when the internal relative humidity of the concrete is greater than 80 percent [3,4].…”
Section: Mitigation Methodsmentioning
confidence: 99%
“…In a study performed on highway median barriers with ASR [3], it was found that the silane-sealed concrete sections reached a much lower relative humidity than the unsealed sections. It was further concluded that silane greatly improved the aesthetics of the barriers for the 10-year study, and the silane was able to stop concrete expansion due to ASR and even caused contraction for at least six years [3].…”
Section: Mitigation Methodsmentioning
confidence: 99%
“…This could have been due to the duration of the wetting cycle. As a result, such a phenomenon could influence the available moisture in concrete for the ASR [ 15 , 78 ].…”
Section: The Role Of Moisture In the Alkali–silica Reactionmentioning
confidence: 99%
“…In existing structures already affected by ASR, there is no known method to halt the reaction. Common mitigation measures include controlling moisture availability through the application of coatings/sealers [ 15 , 16 ], the impregnation of lithium, the release of stresses through slot cutting, and external restraint by post-tensioning [ 17 ]. However, new cracks have been reported to appear years after the application of such techniques [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASR in concrete structures was first identified by Stanton (1940), and considerable research on this topic has been conducted to date, including investigation of the in-situ mechanical properties of reactive mixtures in service (e.g., Clark, 1989;McLeish, 1990;Deschenes et al, 2009;Smaoui et al, 2006), methods to manage the effects of ASR in existing structures (e.g., Fournier et al,2004;Fournier et al, 2010;Charlwood et al, 2012;Bérubé et al, 2002a;Bérubé et al, 2002b;Drimalas et al, 2012) methods to prevent ASR in new structures (e.g., McCoy and Caldwell, 1951;Jensen et al, 1984;Pleau et al, 1989;Lane and Ozyildirim, 1995;Lane and Ozyildirim, 1999;Mather, 1999;Folliard et al, 2006;Bektas et al, 2006;Carles-Gibergues et al, 2008;Thomas et al, 2008;Thomas et al, 2012c;Thomas et al, 2012d) and methods for simulating the effects of ASR on structural components and structures (e.g., Bažant and Steffens 2000;Ulm et al, 2000;Bangert et al, 2004;Saouma and Perotti, 2006;Pesavento et al, 2012;Saouma, 2014) Of particular importance for the present study are investigations into the structural performance of flexural members, specifically those which studied the bond between ASR-affected concrete and deformed bar reinforcement.…”
Section: Introductionmentioning
confidence: 99%